Day 4 Thu, May 07, 2020 2020
DOI: 10.4043/30740-ms
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economical Screening of Chemical EOR Methods for the Offshore

Abstract: Enhanced oil recovery (EOR) and maximizing recovery from declining production fields remain a challenge in the offshore industry. The challenge is to find an EOR method that is both technically and economically feasible considering the high capital and operating costs in the offshore environment. The goal of this work was to conduct a simple cost-benefit analysis based on a technical, facility, and economical screening of chemical EOR methods applicable to the offshore. Offshore Newfoundland, Canada is used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The economic evaluation performed is a simple cost-benefit analysis. It is very useful in determining the economic feasibility of a project through comparison of project cost against the benefits gained from the project . This type of economic evaluation is essential since it only deals in monetary terms …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The economic evaluation performed is a simple cost-benefit analysis. It is very useful in determining the economic feasibility of a project through comparison of project cost against the benefits gained from the project . This type of economic evaluation is essential since it only deals in monetary terms …”
Section: Methodsmentioning
confidence: 99%
“…It is very useful in determining the economic feasibility of a project through comparison of project cost against the benefits gained from the project. 40 This type of economic evaluation is essential since it only deals in monetary terms. 41 The objective of this part of the study is to conduct a normalized economic evaluation of the various ASP formulations.…”
Section: Unit Technical Cost Estimationmentioning
confidence: 99%
“…However, this carbonic acid dissociates very rapidly at ambient conditions to bicarbonate [54], as shown in reaction (7). The bicarbonate electrolyte in the solution can also form 𝐶𝑂 as shown by reaction (8).…”
Section: 𝐶𝑂 (𝑎𝑞) + 𝐻 𝑂 ⇌ 𝐻 𝐶𝑂 (𝑎𝑞)mentioning
confidence: 99%
“…Another advantage for LSWI is that it can be combined with other EOR methods to further improve oil recovery [4][5][6]. According to economic evaluations on chemical EOR methods by Al-Murayri et al [7] and Muriel et al [8], LSWI and CO2 injection generate the highest net present value (NPV) and both methods are effective in increasing oil recovery. Therefore, a hybrid technique termed CO2 low salinity water-alternating-gas (LSWAG) injection, which combines the EOR effect of both methods, has been developed over the last 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Sadeed et al (2018) found the main parameters when optimizing LSWF economics in a Middle Eastern carbonate reservoir were the number and duration of slugs, degree of dilution, and injection and production rates. Based on technical, facility, and economical challenges, Muriel et al (2020) presented a cost-benefit analysis with a focus on offshore fields. The study compared LSWF with alternative chemical EOR methods, such as surfactant flooding, alkaline-surfactant, polymer flooding, alkaline-surfactantpolymer flooding, and nanoparticle injection in two different scenarios: (1) injection from the first day of production (2) injection after secondary production.…”
Section: Economic Evaluationsmentioning
confidence: 99%